Reaktivasi Akuaponik Untuk Ketahanan Pangan Berbasis Rumah Tangga Di Kelurahan Kandri Kecamatan Gunungpati Semarang - Anityas Dian Susanti; Mutiawati Mandaka; Sharfina Bella Pahleva Wahyono; Gatoet Wardianto (BADAN PENERBIT STIEPARI PRESS, 2024)
Aquaponics, as a sustainable agriculture system that combines aquaculture and hydroponics, has become an attractive alternative to growing fish and plants in one container. One example of the implementation of this system is in Kandri Village, Gunungpati Subdistrict, Semarang City, where a thematic village is implementing this concept. The community service effort in the village aims to revive the existing aquaponic system and invite residents to participate in preserving this system so that it can be utilised as a local food source. The community service activities were conducted through a participatory method involving socialisation activities and educational approaches. The goal was to empower the community in terms of sustainability of the aquaponic system. Through this approach, it is expected that the community can understand and practice the basic concepts needed to maintain the sustainability of the system. The impact of this service activity is the return of aquaponic system activities in Kandri Village. This is an important step in maintaining local food security in the area. By reviving this system, the community can utilise the results as a sustainable and environmentally friendly source of additional food. Thus, this community service activity not only provides practical benefits in terms of food fulfilment, but also empowers the community to become more sustainable and environmentally friendly.